3332 Overexpression of CD44 is involved in the development of the early endometriotic lesion in a xenograft model. (27th March 2019) - Knudtson, Jennifer; McLaughlin, Jessica; Santos, Marlen Tellez; Tekmal, Rajeshwar R; Schenken, Robert
Abstract : OBJECTIVES/SPECIFIC AIMS: Previously, we showed decreased development of endometriotic lesions in CD44 knockout mice compared to control.(1) CD44 has 10 different variants and a standard form. Menstrual endometrial cells (MECs) from women with endometriosis have increased adhesion and also express higher levels of CD44 variant 6 (v6) than v3, compared to MECs from women without endometriosis. (2) Here, we assessed the effects of CD44 standard (CD44s), CD44v3 and CD44v6 overexpression (OE) on immortalized human endometrial epithelial (iEECs) and stroma cells (hESCs) in vivo attachment in a nude mouse xenograft model. 1. Knudtson JF, Tekmal RR, Santos MT, et al. Impaired Development of Early Endometriotic Lesions in CD44 Knockout Mice. Reproductive sciences (Thousand Oaks, Calif.). 2016;23(1):87-91. 2. Griffith JS, Liu YG, Tekmal RR, Binkley PA, Holden AE, Schenken RS. Menstrual endometrial cells from women with endometriosis demonstrate increased adherence to peritoneal cells and increased expression of CD44 splice variants. Fertility and sterility. 2010;93(6):1745-1749. METHODS/STUDY POPULATION: Overexpression of CD44s, CD44v3 and CD44v6 was carried out using lipofectamine and their expression verified with qRT-PCR in iEEC and hESCs. Nude mice, 8-10 week old, were injected with estrogen 1 week prior to injection of iEECs and hESCs (n=7 per group). The cells were counted after transfection and at least 300, 000 iEECs and 300, 000 hESCs were injected per mouse. The transfected cells were tagged with cell tracker red (iEECs) and green (hESCs). Forty-eight hours after injection into the xenograft, the mice were sacrificed. The cells were counted using fluorescent stereo microscopy (FSM). Percent attachment was calculated based on the number of cells visualized by FSM divided by the number of transfected cells injected. Unpaired student t-test was performed to analyze differences in the percent attachment of the cells. RESULTS/ANTICIPATED RESULTS: The majority of cells were attached to the peritoneum. There was increased attachment of hESCs with OE of CD44v6 compared to control (p=0.03). CD44v6 OE did not change attachment of iEECs. There was no difference in attachment in iEECs or hESCs with OE of CD44s or CD44v3. DISCUSSION/SIGNIFICANCE OF IMPACT: Overexpression of CD44v6 increases attachment of ESCs to PMCs in an in vivo xenograft model. Menstrual endometrial cell type and CD44 variants play a complex role in the development of the early endometriotic lesion.